The Influence of Intertextuality on Aesthetic Principles in Postmodernist Painting and Architecture - Damirchi Loo, Leila (Salehan Institute of Higher Education, 2018)
Intertextuality reflects certain studies theories shaped in recent decades and has been widely used in artistic and literary studies as well as other studies in the field of Humanities. Intertextuality is not merely a theoretical notion in literary studies since its influence embraces the intellectual and cultural field as a whole. Intertextuality not only challenges many traditional beliefs, but also addresses the fact that a culture is constantly seeking to prove its own originality and identity through suppressing plurality, diversity, altruism, and dissent shall never tolerate the inevitable consequences of this concept. On the other hand, as a cultural and historical term, Postmodernism often invokes in one’s mind notions of hybridization, emulation, and combination of pre-established styles and trends. In the same way, contemporary art relies on certain visually distinguishable images of classical paintings. Apparently, Intertextuality serves to highlight the important notions of the fundamental relationship as well as the mutual bond and interdependence in today’s cultural existence. This article studies how Intertextuality as a way of thinking has influenced the development of various painting and architectural styles. For this purpose, we first define Intertextuality and investigate how and why it has come to encompass its present meanings and applications.